Cognitive Obstacles and Textbook Praxeological Limitations Underlying The Low Mathematical Creative Thinking of Elementary Students - Ghany Taufik Sidik; Tatang Herman; Sufyani Prabawanto; Arie Rakhmat Riyadi; Mohd Salehudin Marji (FKIP Universitas Lampung, 2026)
The importance of mathematical creative thinking skills in the 21st century differs from the creative thinking skills of current elementary school students. A 5th-grade student at a public elementary school in West Bandung Regency, Indonesia, has low levels of creative thinking. This study aimed to analyze fifth-grade students' mathematical creative thinking skills during problem-solving, identify the underlying causes of their low performance, and propose instructional strategies to foster their development. The method used was qualitative, with a descriptive–interpretive design. Participants comprised 15 fifth-grade students from a single public elementary school in West Bandung Regency, Indonesia, selected via convenience sampling. The primary research instrument was the researcher, supported by a creative thinking skills test instrument and an interview guide. The results of this study are 1 student had a high level of creative thinking skills able to achieve indicators of flexibility, originality, awareness, and elaboration; 1 student had a moderate level of creative thinking skills able to achieve indicators of originality, awareness, and elaboration; and 13 students had low levels of creative thinking skills able to achieve indicators of fluency/originality/awareness/originality and awareness/ had not even achieved all indicators of mathematical creative thinking skills. Further analysis revealed fundamental misconceptions, particularly confusion between area and perimeter, fragmented procedural reasoning, and limited metacognitive verification during mathematical problem-solving. To improve students’ creative thinking skills, it is recommended to use learning activities oriented towards problem- and project-based learning, realistic mathematics, and mathematics textbooks that also support the problem-solving process. In conclusion, most fifth-grade students demonstrate low levels of mathematical creative thinking skills, shaped by conceptual misconceptions and limited metacognitive regulation, underscoring the importance of targeted, conceptually grounded, and problem-oriented instructional interventions. Keywords: creative thinking skills, mathematics, problem-solving.